Oxapolycycles from one-pot cross-metathesis/carbonyl ylide formation-intramolecular cycloaddition of alpha-diazo-beta-keto esters - Hodgson, D; Angrish, D (2006)
Chemoselective cross-metathesis of unsaturated α-diazo-β-keto esters using Grubbs' 2nd generation catalyst, followed by Rh 2(OAc)4-catalysed tandem carbonyl ylide formation-intramolecular cycloaddition is demonstrated. The two different catalytic metallocarbene transfer reactions have also been successfully carried out in a one-pot procedure, which allows rapid generation of molecular complexity in a single operation. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.